MALEATE ENALAPRIL INFLUENCE ON NEUROGOMORAL REGULATION OF HEALTHY VOLUNTEERS - Isaeva, A.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The maleate enalapril (20 mg was taken) influence on neurohumoral regulation (NHR) state of healthy volunteers (13 women and 2 men of the average age of 24) was studied in acute pharmacological test. The spatially temporal and spectral indexes of heart rate variability, blood pressure were used for assessing state. The blood pressure and rhythmogram were registered in second standard horizontal position of the electrocardiograph and as well as in vertical (active tilt-test) one before the maleate enalapril administration and 180 minutes after it. The blood pressure was measured by Korotkov’s method and the rhythmogram was registered with the help of computer electrocardiograph «Cardiolab 2000». Fourier’s method of quick transformation was used for getting spectral HRV characteristics, 5 and 7 minutes recordings of electrocardiograph in second standard position were analyzed. Statistic data analysis was performed with the help of Excel for Windows’98. The authenticity of the differences between the groups was determined with the help of a non-parametric sign test and Wilkokson T-criterium for 95% confidence interval. Enalapril maleate increased the total power of without changes in sympathoparasympathetic balance, intensified the NHR system reaction on active tilt test with more significant changes in humoral and sympathetic domains. Positive effects of enalapril maleate on the quality and length of life  may be connected with his ability to improve the NHR state.